Orientacja agroenergetyczna użytkowników towarowych gospodarstw rolnych regionu opolskiego. Uwarunkowania instytucjonalne - Bisaga, Anna (Agroenergetic Orientation of Commodity Users of Farms in Opole Area. Institutional Conditioning, 2009)
The reform of CAP in 2003 validated a new model of European agriculture as multifunctional, which also foresees agroenergetic orientation of farms. In Polish conditions the structures of agriculture co-management resulting from II Common Agricultural Policy are implemented faster on "green market" than on traditional food market. This article presents the results of research that concern the influence of agriculture structure on agroenergetic orientation of commodity users of farms in Opole area and deliberations on its influence on agriculture shape in the region and new agriculture economics.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 254-263